Overboard - Greenberg, Rob; Fisher, Bob (Screenwriter); Dixon, Leslie; Derbez, Eugenio; Odell, Benjamin, 1969-; Faris, Anna, 1976-; Longoria, Eva, 1975-; Hannah, John, 1962-; Pantelion Films (Firm); Metro-Goldwyn-Mayer (1992- ); 3Pas Studios (Pantelion Films, 2018)
When Leonardo, a wealthy businessman, has a yachting accident and develops amnesia, an ill-treated employee exacts some revenge. Kate is a single mom who manages to convince Leonardo that she is his wife. Hilarity ensues as Leonardo must take on the task of helping Kate raise her three daughters. Will Kate's plan succeed to perfection, or will she discover that Leonardo isn't such a bad guy after all? It's classic role reversal in this remake of an iconic comedy.
Originally released as a motion picture in 2018.
Remake of the 1987 film of the same name written by Leslie Dixon and directed by Garry Marshall.
Special features: Audio commentary with writer-director Rob Greenberg, writer Bob Fisher, and producer Benjamin Odell; Chemistry is comedy; Culture clash; Captains of the ship: Bob & Rob.
Costume designer, Karin Nosella ; music, Lyle Workman ; editor, Lee Haxall ; production designer, Brent Thomas ; director of photography, Michal Barrett.
Anna Faris, Eva Longoria, Eugenio Derbez, John Hannah.
MPAA rating: PG-13; for suggestive material, partial nudity and some language.
Keywords: Revenge -- Drama; Man-woman relationships -- Drama; Romance films; Comedy films; Film remakes; Video recordings for the hearing impaired; Video recordings for people with visual disabilities